High-uniformity quantum dot diffusion plate and preparation method thereof
By using acrylic copolymer matrix, CdSe/ZnS core-shell structure quantum dots and multi-stage photodiffusion agent systems in quantum dot diffusion plates, combined with multiple functional additives, the agglomeration, low light efficiency and stability of quantum dot diffusion plates are solved. Problem, high uniformity and long life quantum dot diffusion plates are achieved.
Patent Information
- Application Number
- CN202411617487.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing quantum dot diffusion plate technology has problems such as quantum dot agglomeration, low light efficiency, local heat spots, and material instability, making it difficult to realize high-performance display devices.
Acrylic copolymer matrix, CdSe/ZnS core-shell structure quantum dots, multi-stage photodiffusion agent system and multiple functional additives are used to form a high-uniform quantum dot diffusion plate through chemical bonding, multi-scale optical regulation and multiple stability protection.
It significantly improves the luminescence uniformity, optical performance and stability of the quantum dot diffusion plate, extends the service life, and achieves the comprehensive performance improvement of the quantum dot-polymer composite system.
Smart Images

Figure BDA0005132619240000151 
Figure BDA0005132619240000152 
Figure BDA0005132619240000161
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of quantum dot diffusion plates, and in particular to a high-uniformity quantum dot diffusion plate and a preparation method thereof. Background Art
[0002] With the rapid development of display technology, quantum dot technology has shown broad application prospects in the field of new-generation displays due to its excellent color purity and wide color gamut characteristics. At present, quantum dot diffuser is a key component for realizing quantum dot display, and its performance directly affects the overall performance of display devices. However, existing quantum dot diffuser technology still faces many challenges.
[0003] First, in terms of quantum dot dispersion, traditional technologies mainly rely on simple physical dispersion methods and lack precise control of the chemical environment on the surface of quantum dots. This causes quantum dots to easily agglomerate in the polymer matrix, which not only reduces the quantum efficiency but also causes uneven luminescence. In particular, when the concentration of quantum dots increases, the agglomeration phenomenon becomes more significant, which seriously restricts the improvement of device performance.
[0004] Secondly, the existing technology is relatively simple in the selection and design of light diffusers, usually using a single particle size or a simple mixed light diffusion system. This method is difficult to achieve precise control of light of different scales, resulting in low light output efficiency and prone to local hot spots, which affects the service life of the device.
[0005] Thirdly, traditional polymer matrix design often overemphasizes a certain performance index, such as light transmittance or mechanical strength, while ignoring the balance between various properties. For example, reducing the cross-linking degree to improve light transmittance leads to decreased thermal stability; or increasing the cross-linking density to increase mechanical strength causes material embrittlement and affects processing performance.
[0006] Finally, in terms of stability, the existing technology mainly relies on a single type of stabilizer and cannot establish a comprehensive protection system. This makes the quantum dot diffusion plate prone to aging phenomena such as light attenuation and yellowing in actual applications, seriously affecting the service life of the product. Summary of the invention
[0007] In view of the above problems, the present invention provides a high-uniformity quantum dot diffusion plate and a preparation method thereof.
[0008] The object of the present invention is to provide a high uniformity quantum dot diffusion plate, which comprises the following components by weight:
[0009] 920-940 parts by weight of acrylic copolymer matrix, 20-30 parts by weight of CdSe / ZnS core-shell structure quantum dots, 25-35 parts by weight of light diffuser system, and 12-18 parts by weight of functional additive combination;
[0010] The acrylic copolymer matrix is composed of the following monomers: 455-475 parts by weight of methyl methacrylate, 270-288 parts by weight of butyl acrylate, 134-144 parts by weight of styrene, and 44-50 parts by weight of glycidyl methacrylate.
[0011] Preferably, the CdSe / ZnS core-shell structure quantum dots include:
[0012] The core layer CdSe is 16-18 parts by weight, with a particle size of 3.3-3.7 nm;
[0013] The shell layer contains 7-9 parts by weight of ZnS and has a shell layer thickness of 0.4-0.6 nm.
[0014] Preferably, the light diffuser system comprises:
[0015] Barium sulfate 11-13 parts by weight, particle size 75-85nm;
[0016] 9-11 parts by weight of silicon dioxide, with a particle size of 95-105 nm;
[0017] 7-9 parts by weight of polymethyl methacrylate microspheres, with a particle size of 2.8-3.2 μm.
[0018] Preferably, the functional additive combination comprises:
[0019] 2.5-3.5 parts by weight of UV stabilizer compound system;
[0020] 3.5-4.5 parts by weight of antioxidant synergistic system;
[0021] Surface conditioner 7-9 parts by weight.
[0022] Preferably, the UV stabilizer compounding system comprises:
[0023] 1577 1.6-2.0 parts by weight;
[0024] 329 0.9-1.5 parts by weight;
[0025] The antioxidant synergistic system comprises:
[0026] BHT 1.4-1.8 parts by weight;
[0027] 168 1.2-1.6 parts by weight;
[0028] PS 802 0.9-1.1 parts by weight;
[0029] The surface conditioner comprises:
[0030] L-7602 1.8-2.2 parts by weight;
[0031] F-127 1.8-2.2 parts by weight;
[0032] 4-methoxyphenol 1.8-2.2 parts by weight;
[0033] 1.8-2.2 parts by weight of polymethacrylate sodium salt.
[0034] The method for preparing the quantum dot diffusion plate comprises the following steps:
[0035] Step (1): preparing an acrylic copolymer matrix;
[0036] Step (2): preparing a quantum dot diffusion layer;
[0037] Step (3): bonding the quantum dot diffusion layer to a substrate.
[0038] Preferably, the step (1) comprises:
[0039] (1.1) Purifying the monomers by vacuum distillation at a pressure of 90-110 mmHg, wherein the distillation temperature of methyl methacrylate is 33-37° C., the distillation temperature of butyl acrylate is 63-67° C., and the distillation temperature of styrene is 43-47° C.;
[0040] (1.2) Methyl methacrylate, butyl acrylate, styrene and glycidyl methacrylate are added dropwise in order at 70-80° C. according to the formula ratio, and 2.8-3.2 parts by weight of azobisisobutyronitrile are added, and the mixture is reacted at 70-80° C. for 3.5-4.5 hours.
[0041] Preferably, the step (2) comprises:
[0042] (2.1) Ultrasonic dispersion of the light diffuser in toluene at a frequency of 35-45 kHz, a temperature of 23-27° C., and a time of 25-35 minutes;
[0043] (2.2) adding quantum dot dispersion and functional additive combination in sequence, stirring and mixing at 130-170 rpm for 60 minutes;
[0044] (2.3) Add the acrylic copolymer prepared in step (1) and stir at 30±2°C for 120 minutes.
[0045] Preferably, the quantum dot diffusion layer obtained in step (2) is dried in three stages:
[0046] The first stage: drying at 35-45℃ for 12-18 minutes;
[0047] The second stage: drying at 55-65℃ for 18-22 minutes;
[0048] The third stage: drying at 75-85℃ for 8-12 minutes.
[0049] Preferably, the step (3) comprises:
[0050] (3.1) Plasma cleaning of the substrate at a power of 35-45 W for 25-35 seconds;
[0051] (3.2) Laminating at 83-87°C, 0.55-0.65 MPa for 2.5-3.5 minutes;
[0052] (3.3) After naturally cooling to room temperature, perform aging treatment at 55-65°C for 22-26 hours.
[0053] The present invention has the following beneficial effects:
[0054] Based on in-depth research on quantum dot-polymer composite systems, the present invention has developed a new type of quantum dot diffusion plate with high uniformity and a preparation method thereof. Through molecular design and process innovation, the present invention has achieved the following technical breakthroughs:
[0055] From the perspective of molecular structure design, the present invention introduces epoxy groups into the acrylic copolymer and utilizes the chemical bonding between the epoxy groups and the ligands on the surface of the quantum dots to form a stable coordination structure. This chemical bonding not only provides a steric hindrance effect, but also enhances the energy transfer efficiency through orbital hybridization. In particular, the ring-opening reaction of the epoxy groups forms a covalent connection at the interface, which significantly improves the stability of the system.
[0056] In terms of the light diffusion system, the present invention creatively designs a "nano-submicron-micron" three-level light diffusion structure. By precisely controlling the spatial distribution of diffusants of different scales, a complete photon transmission network is constructed. Nano-scale barium sulfate is mainly responsible for near-field scattering, submicron-scale silica provides mid-range regulation, and micron-scale PMMA microspheres achieve far-field homogenization. This multi-level structure not only improves the light extraction efficiency, but also significantly improves the luminescence uniformity.
[0057] In terms of stability design, the present invention has developed a multiple synergistic protection system of "steric hindrance-free radical capture-peroxide decomposition". Triazine UV stabilizers absorb ultraviolet light through n-π* transition, while benzotriazoles consume excited state energy through proton transfer mechanism. At the same time, hindered phenol antioxidants capture free radicals through hydrogen donation mechanism, and phosphites decompose peroxides through reduction. This multiple protection mechanism ensures the long-term stability of the material under various environmental conditions.
[0058] The technical solution of the present invention achieves a comprehensive improvement in the performance of the quantum dot diffusion plate through precise design at the molecular level and multi-scale structural regulation. It is particularly worth mentioning that the present invention has also discovered some unexpected synergistic effects: for example, the introduction of epoxy groups not only enhances the interface bonding, but also optimizes the luminescence environment of the quantum dots through local polarity regulation; the multi-level light diffusion system not only improves the optical properties, but also plays a role in stress dispersion and improves the mechanical strength of the material.
[0059] In summary, the present invention successfully solves the key problems in the prior art through innovative designs such as chemical bonding, multi-scale optical regulation and multiple stability protection, and provides a new technical path for the development of high-performance quantum dot diffusion plates. DETAILED DESCRIPTION
[0060] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0061] Example 1
[0062] This embodiment provides a high uniformity quantum dot diffusion plate and a preparation method thereof. The quantum dot diffusion plate comprises the following components by weight: 920 parts by weight of acrylic copolymer matrix, 20 parts by weight of CdSe / ZnS core-shell structure quantum dots, 25 parts by weight of light diffuser system, and 12 parts by weight of functional auxiliary agent combination.
[0063] The acrylic copolymer matrix is composed of the following monomers: 455 parts by weight of methyl methacrylate, 270 parts by weight of butyl acrylate, 134 parts by weight of styrene, and 44 parts by weight of glycidyl methacrylate. This monomer ratio can preferably achieve high light transmittance and moderate mechanical strength, while providing good interface bonding performance through the introduction of glycidyl methacrylate.
[0064] The CdSe / ZnS core-shell structure quantum dots include: 16 parts by weight of CdSe core layer (particle size 3.3nm) and 7 parts by weight of ZnS shell layer (shell thickness 0.4nm). In the present invention, narrowband emission and high quantum yield can be achieved by precisely controlling the size of the core-shell structure.
[0065] The light diffuser system includes: 11 parts by weight of barium sulfate with a particle size of 75 nm, 9 parts by weight of silicon dioxide with a particle size of 95 nm, and 7 parts by weight of polymethyl methacrylate microspheres with a particle size of 2.8 μm. This light diffuser ratio with multi-level particle size distribution can achieve multi-scale control of light and significantly improve light extraction efficiency.
[0066] The functional additive combination comprises:
[0067] 2.5 parts by weight of UV stabilizer compound system, including 1577 1.6 parts by weight, 3290.9 parts by weight;
[0068] 3.5 parts by weight of antioxidant synergistic system, including BHT 1.4 parts by weight, 168 1.2 parts by weight, PS 802 0.9 parts by weight;
[0069] 7 parts by weight of surface conditioner, including L-7602 1.8 parts by weight, F-127 1.8 parts by weight, 4-methoxyphenol 1.8 parts by weight, polymethacrylate sodium salt 1.8 parts by weight.
[0070] Preferably, the synergistic combination of the above functional additives can form a multiple protection network, significantly improving the light and heat stability and storage stability of the product.
[0071] The preparation method of the quantum dot diffusion plate comprises the following steps:
[0072] Step (1) preparing an acrylic copolymer matrix:
[0073] First, the monomers were purified by vacuum distillation with the pressure controlled at 90 mmHg, wherein the distillation temperature of methyl methacrylate was 33°C, the distillation temperature of butyl acrylate was 63°C, and the distillation temperature of styrene was 43°C.
[0074] Then, methyl methacrylate, butyl acrylate, styrene and glycidyl methacrylate were added dropwise in sequence at 70° C. according to the above-mentioned ratio, and 2.8 parts by weight of azobisisobutyronitrile were added, and the mixture was reacted at 70° C. for 3.5 hours under nitrogen protection.
[0075] Step (2) Preparation of quantum dot diffusion layer:
[0076] First, the light diffuser was dispersed in toluene by ultrasonication at a frequency of 35 kHz, a temperature of 23°C, and a time of 25 minutes;
[0077] Secondly, the quantum dot dispersion and the functional additive combination were added in sequence, and the mixture was stirred and mixed at 130 rpm for 60 minutes;
[0078] Then, the acrylic acid copolymer prepared in step (1) was added and stirred at 30° C. for 120 minutes;
[0079] Finally, three stages of drying were performed: 35°C for 12 minutes, 55°C for 18 minutes, and 75°C for 8 minutes.
[0080] Step (3) Lamination:
[0081] First, the substrate was plasma cleaned at a power of 35 W for 25 seconds;
[0082] Then, the bonding was performed at 83°C and 0.55 MPa for 2.5 minutes;
[0083] Finally, after naturally cooling to room temperature, the samples were aged at 55°C for 22 hours.
[0084] Example 2
[0085] This embodiment provides a high uniformity quantum dot diffusion plate and a preparation method thereof. The quantum dot diffusion plate comprises the following components by weight: 930 parts by weight of acrylic copolymer matrix, 25 parts by weight of CdSe / ZnS core-shell structure quantum dots, 30 parts by weight of light diffuser system, and 15 parts by weight of functional auxiliary agent combination.
[0086] The acrylic copolymer matrix is composed of the following monomers: 465 parts by weight of methyl methacrylate, 279 parts by weight of butyl acrylate, 139 parts by weight of styrene, and 47 parts by weight of glycidyl methacrylate. Preferably, this medium ratio of monomers achieves a good balance between light transmittance and mechanical strength, and has excellent film-forming properties.
[0087] The CdSe / ZnS core-shell structure quantum dots include: 17 parts by weight of CdSe core layer (particle size 3.5 nm) and 8 parts by weight of ZnS shell layer (shell thickness 0.5 nm). This core-shell size ratio can achieve the best luminous efficiency while ensuring the stability of quantum dots.
[0088] The light diffuser system includes: 12 parts by weight of barium sulfate with a particle size of 80 nm, 10 parts by weight of silicon dioxide with a particle size of 100 nm, and 8 parts by weight of polymethyl methacrylate microspheres with a particle size of 3.0 μm. The multi-stage light diffusion system in this embodiment achieves efficient scattering and uniform distribution of light through a reasonable particle size gradient distribution.
[0089] The functional additive combination comprises:
[0090] 3.0 parts by weight of UV stabilizer compound system, including 1577 1.8 parts by weight, 3291.2 parts by weight;
[0091] 4.0 parts by weight of antioxidant synergistic system, wherein BHT 1.6 parts by weight, 168 1.4 parts by weight, PS 802 1.0 parts by weight;
[0092] 8 parts by weight of surface conditioner, including L-7602 2.0 parts by weight, F-127 2.0 parts by weight, 4-methoxyphenol 2.0 parts by weight, polymethacrylate sodium salt 2.0 parts by weight.
[0093] The preparation method of the quantum dot diffusion plate comprises the following steps:
[0094] Step (1) preparing an acrylic copolymer matrix:
[0095] First, the monomers were purified by vacuum distillation with the pressure controlled at 100 mmHg, wherein the distillation temperature of methyl methacrylate was 35°C, the distillation temperature of butyl acrylate was 65°C, and the distillation temperature of styrene was 45°C.
[0096] Then, methyl methacrylate, butyl acrylate, styrene and glycidyl methacrylate were added dropwise in sequence at 75° C. according to the above-mentioned ratio, and 3.0 parts by weight of azobisisobutyronitrile were added, and the mixture was reacted at 75° C. for 4.0 hours under nitrogen protection.
[0097] Step (2) Preparation of quantum dot diffusion layer:
[0098] First, the light diffuser was dispersed in toluene by ultrasonication at a frequency of 40 kHz, a temperature of 25°C, and a time of 30 minutes;
[0099] Secondly, the quantum dot dispersion and the functional additive combination were added in sequence, and stirred and mixed at 150 rpm for 60 minutes;
[0100] Then, the acrylic acid copolymer prepared in step (1) was added and stirred at 30° C. for 120 minutes;
[0101] Finally, three stages of drying were performed: 40°C for 15 minutes, 60°C for 20 minutes, and 80°C for 10 minutes.
[0102] Step (3) Lamination:
[0103] First, the substrate was plasma cleaned at a power of 40 W for 30 seconds;
[0104] Then, the lamination was performed at 85°C and 0.60 MPa for 3.0 minutes;
[0105] Finally, after cooling naturally to room temperature, the samples were aged at 60°C for 24 hours.
[0106] Example 3
[0107] This embodiment provides a high uniformity quantum dot diffusion plate and a preparation method thereof. The quantum dot diffusion plate comprises the following components by weight: 940 parts by weight of acrylic copolymer matrix, 30 parts by weight of CdSe / ZnS core-shell structure quantum dots, 35 parts by weight of light diffuser system, and 18 parts by weight of functional auxiliary agent combination.
[0108] The acrylic copolymer matrix is composed of the following monomers: 475 parts by weight of methyl methacrylate, 288 parts by weight of butyl acrylate, 144 parts by weight of styrene, and 50 parts by weight of glycidyl methacrylate. This high ratio of monomers provides excellent weather resistance and toughness.
[0109] The CdSe / ZnS core-shell structure quantum dots include: 18 parts by weight of CdSe core layer (particle size 3.7nm) and 9 parts by weight of ZnS shell layer (shell thickness 0.6nm). Preferably, this larger core-shell structure not only provides a higher quantum yield, but also significantly improves the photothermal stability.
[0110] The light diffuser system includes: 13 parts by weight of barium sulfate with a particle size of 85 nm, 11 parts by weight of silicon dioxide with a particle size of 105 nm, and 9 parts by weight of polymethyl methacrylate microspheres with a particle size of 3.2 μm. In this embodiment, the synergistic effect of the three light diffusers forms a complete scattering network, effectively preventing direct light transmission.
[0111] The functional additive combination comprises:
[0112] 3.5 parts by weight of UV stabilizer compound system, including 1577 2.0 parts by weight, 3291.5 parts by weight;
[0113] 4.5 parts by weight of antioxidant synergistic system, including BHT 1.8 parts by weight, 168 1.6 parts by weight, PS 802 1.1 parts by weight;
[0114] 9 parts by weight of surface conditioner, wherein L-7602 2.2 parts by weight, F-127 2.2 parts by weight, 4-methoxyphenol 2.2 parts by weight, polymethacrylate sodium salt 2.2 parts by weight.
[0115] The preparation method of the quantum dot diffusion plate comprises the following steps:
[0116] Step (1) preparing an acrylic copolymer matrix:
[0117] First, the monomers were purified by vacuum distillation with the pressure controlled at 110 mmHg, wherein the distillation temperature of methyl methacrylate was 37°C, the distillation temperature of butyl acrylate was 67°C, and the distillation temperature of styrene was 47°C.
[0118] Then, methyl methacrylate, butyl acrylate, styrene and glycidyl methacrylate were added dropwise in sequence at 80° C. according to the above-mentioned ratio, and 3.2 parts by weight of azobisisobutyronitrile were added, and the mixture was reacted at 80° C. for 4.5 hours under nitrogen protection.
[0119] Step (2) Preparation of quantum dot diffusion layer:
[0120] First, the light diffuser was dispersed in toluene by ultrasonication at a frequency of 45 kHz, a temperature of 27°C, and a time of 35 minutes;
[0121] Secondly, the quantum dot dispersion and the functional additive combination were added in sequence, and the mixture was stirred and mixed at 170 rpm for 60 minutes;
[0122] Then, the acrylic acid copolymer prepared in step (1) was added and stirred at 30° C. for 120 minutes;
[0123] Finally, three stages of drying were performed: 45°C for 18 minutes, 65°C for 22 minutes, and 85°C for 12 minutes.
[0124] Step (3) Lamination:
[0125] First, the substrate was plasma cleaned at a power of 45 W for 35 seconds;
[0126] Then, the bonding was performed at 87°C and 0.65MPa for 3.5 minutes;
[0127] Finally, after naturally cooling to room temperature, the samples were aged at 65°C for 26 hours.
[0128] Example 4
[0129] This embodiment provides a high uniformity quantum dot diffusion plate and a preparation method thereof. The quantum dot diffusion plate comprises the following components by weight: 935 parts by weight of acrylic copolymer matrix, 27 parts by weight of CdSe / ZnS core-shell structure quantum dots, 32 parts by weight of light diffuser system, and 16 parts by weight of functional auxiliary agent combination.
[0130] The acrylic copolymer matrix is composed of the following monomers: 470 parts by weight of methyl methacrylate, 284 parts by weight of butyl acrylate, 142 parts by weight of styrene, and 48 parts by weight of glycidyl methacrylate. This embodiment adopts such a medium to high monomer ratio to obtain excellent processing performance while ensuring optical properties.
[0131] The CdSe / ZnS core-shell structure quantum dots include: 17.5 parts by weight of CdSe core layer (particle size 3.6 nm) and 8.5 parts by weight of ZnS shell layer (shell thickness 0.55 nm). Preferably, the design of this core-shell structure achieves the best balance between luminous efficiency and stability.
[0132] The light diffuser system includes: 12.5 parts by weight of barium sulfate with a particle size of 82 nm, 10.5 parts by weight of silicon dioxide with a particle size of 102 nm, and 8.5 parts by weight of polymethyl methacrylate microspheres with a particle size of 3.1 μm. The best optical uniformity is achieved by precisely controlling the particle size and ratio of the three light diffusers.
[0133] The functional additive combination comprises:
[0134] 3.2 parts by weight of UV stabilizer compound system, including 1577 1.9 parts by weight, 3291.3 parts by weight;
[0135] 4.2 parts by weight of antioxidant synergistic system, including BHT 1.7 parts by weight, 168 1.5 parts by weight, PS 802 1.0 parts by weight;
[0136] 8.6 parts by weight of surface conditioner, including L-7602 2.1 parts by weight, F-127 2.1 parts by weight, 4-methoxyphenol 2.1 parts by weight, polymethacrylate sodium salt 2.1 parts by weight.
[0137] The preparation method of the quantum dot diffusion plate comprises the following steps:
[0138] Step (1) preparing an acrylic copolymer matrix:
[0139] First, the monomers were purified by vacuum distillation with the pressure controlled at 105 mmHg, wherein the distillation temperature of methyl methacrylate was 36°C, the distillation temperature of butyl acrylate was 66°C, and the distillation temperature of styrene was 46°C.
[0140] Then, methyl methacrylate, butyl acrylate, styrene and glycidyl methacrylate were added dropwise in sequence at 77° C. according to the above-mentioned ratio, and 3.1 parts by weight of azobisisobutyronitrile were added, and the mixture was reacted at 77° C. for 4.2 hours under nitrogen protection.
[0141] Step (2) Preparation of quantum dot diffusion layer:
[0142] First, the light diffuser was dispersed in toluene by ultrasonication at a frequency of 42 kHz, a temperature of 26°C, and a time of 32 minutes;
[0143] Secondly, the quantum dot dispersion and the functional additive combination were added in sequence, and the mixture was stirred and mixed at 160 rpm for 60 minutes;
[0144] Then, the acrylic acid copolymer prepared in step (1) was added and stirred at 30° C. for 120 minutes;
[0145] Finally, three stages of drying were performed: 42°C for 16 minutes, 62°C for 21 minutes, and 82°C for 11 minutes.
[0146] Step (3) Lamination:
[0147] First, the substrate was plasma cleaned with a power of 42 W and a time of 32 seconds;
[0148] Then, the bonding was performed at 86°C and 0.62MPa for 3.2 minutes;
[0149] Finally, after naturally cooling to room temperature, the samples were aged at 62°C for 25 hours.
[0150] Comparative Example 1 (corresponding to Example 1, verifying the importance of quantum dot ratio)
[0151] This comparative example uses the same components and preparation method as Example 1, except that the amount of CdSe / ZnS core-shell structure quantum dots is reduced to 15 parts by weight (lower than the lower limit of the claim), wherein the core layer CdSe is reduced to 14 parts by weight, and the shell layer ZnS is reduced to 6 parts by weight. The other components and preparation process are exactly the same as those in Example 1.
[0152] Through comparative tests, it was found that due to insufficient quantum dot content, the luminescence intensity of the sample was significantly reduced, and the quantum yield was only 65%, which was significantly lower than 85% in Example 1. This result shows that the quantum dot dosage range (20-30 parts by weight) set by the present invention is a necessary condition for maintaining high luminescence efficiency. Further research found that low-content quantum dots are difficult to form an effective energy transfer network, resulting in reduced utilization efficiency of excitation energy.
[0153] Comparative Example 2 (corresponding to Example 2, verifying the synergistic effect of the light diffusing agent)
[0154] In this comparative example, the three-component light diffuser system in Example 2 is replaced with a single barium sulfate of 30 parts by weight, and the total amount is the same as that in Example 2. The other components and preparation process remain unchanged.
[0155] The test results show that although the total transmittance of the samples is similar, the uniformity of light distribution is significantly reduced. Laser confocal microscopy observations show that the light diffuser with a single particle size cannot form a multi-scale scattering network, resulting in obvious light intensity differences in local areas, and the relative standard deviation reaches 15%, which is much higher than 5% in Example 2. This fully proves that the multi-level light diffusion system used in the present invention has a unique synergistic effect.
[0156] Comparative Example 3 (corresponding to Example 3, verifying the ratio relationship of the functional additives)
[0157] This comparative example keeps the overall formula of Example 3 unchanged, but adjusts the ratio of the functional additive combination: 1577 and The ratio of 329 was changed from 4:3 to 1:1.
[0158] The accelerated aging test showed that after 1000 hours of ultraviolet irradiation, the luminous intensity of the sample with the adjusted ratio decayed by 8%, which was significantly higher than the 3% in Example 3. Infrared spectrum analysis showed that this ratio change destroyed the complementary protective effect of the two ultraviolet stabilizers in different wavelength regions, causing a significant decrease in light stability.
[0159] Comparative Example 4 (corresponding to Example 4, verifying the key parameters of the preparation process)
[0160] This comparative example adopts the same formulation as that of Example 4, but the three-stage drying process of the quantum dot diffusion layer is changed to a single-stage drying (60° C., 45 minutes).
[0161] The test found that the sample surface using the single-stage drying process had obvious stress cracking, and the interface bonding strength was reduced by 30%. Dynamic mechanical analysis confirmed that this was due to the uneven evaporation of the solvent caused by rapid drying, which formed a large internal stress. This verifies the importance of the three-stage drying process used in the present invention for product quality.
[0162] Comparative Example 5 (Verification of the criticality of the composition of acrylic copolymer)
[0163] In this comparative example, the amount of glycidyl methacrylate is increased to 55 parts by weight (exceeding the upper limit of the claim), and the amount of methyl methacrylate is reduced accordingly. Other components and process parameters are the same as those in Example 2.
[0164] The results show that excessive epoxy groups lead to excessive crosslinking of the material, making the product brittle and hard, and significantly reducing flexibility. In the tensile test, the elongation at break is only 45% of that in Example 2. This confirms that the precise control of the composition ratio of each monomer in the present invention is of great significance.
[0165] Comparative Example 6 (Verification of the synergy of process parameters)
[0166] This comparative example is based on the formulation of Example 3, but the following process parameters are changed at the same time:
[0167] The ultrasonic dispersion time of the light diffuser is shortened to 20 minutes;
[0168] The lamination pressure is increased to 0.7MPa;
[0169] The aging temperature was increased to 70°C;
[0170] Comprehensive test results show that deviations from multiple process parameters lead to significant degradation of product performance:
[0171] The dispersion of the light diffuser deteriorated, and the number of agglomerated particles increased by 150%;
[0172] Too strong interface bonding strength will lead to local deformation;
[0173] The yellowing index after accelerated aging increased by 1.8 times.
[0174] Performance testing and evaluation
[0175] In order to comprehensively evaluate the performance of the quantum dot diffusion plate of the present invention, a systematic test scheme was established. First, the optical properties were characterized, including quantum yield, spectral characteristics, and light diffusion uniformity; second, the stability of the material was evaluated, including photothermal stability and environmental durability; finally, the mechanical properties and interface bonding were tested. The specific test methods are as follows:
[0176] 1. Optical performance test
[0177] Test equipment: Edinburgh FLS1000 fluorescence spectrometer equipped with integrating sphere accessory.
[0178] Test conditions: room temperature 25±1℃, relative humidity 45±5%.
[0179] Quantum yield test: using the integrating sphere method, the excitation wavelength is 365nm, the scanning range is 400-700nm, and the slit width is 2nm.
[0180] Spectral uniformity: Divide the sample into 9 areas, measure the central wavelength and half-peak width, and calculate the relative standard deviation.
[0181] 2. Stability Assessment
[0182] Photothermal aging: Xenon lamp aging box, light intensity 6000cd / m 2 , temperature 85±2℃.
[0183] Environmental aging: Constant temperature and humidity chamber, 60℃ / 90%RH.
[0184] Test cycle: 0h, 250h, 500h, 750h, 1000h.
[0185] 3. Mechanical properties test
[0186] Tensile properties: CMT4104 universal testing machine was used with a tensile rate of 5 mm / min.
[0187] Peel strength: T-type peel test, peel rate 100mm / min.
[0188] Hardness: Shore D hardness tester, load 1kg.
[0189] [Table 1] Optical performance test results
[0190]
[0191] [Table 2] Stability test results (after 1000h)
[0192]
[0193] Through comprehensive analysis of the test results, the present invention shows the following unexpected technical effects:
[0194] First, in terms of optical performance, Example 2 performs the best, with a quantum yield of 87.6% while maintaining extremely high light uniformity (97.2%). This excellent performance stems from the unique multi-stage light diffusion system design of the present invention, which forms an efficient light regulation network by precisely controlling the ratio of light diffusers of different sizes. It is particularly noteworthy that when the particle size ratio of the light diffuser meets the requirements of the present invention, the best scattering effect can be achieved while maintaining high light transmittance.
[0195] Secondly, in terms of stability, Example 3 showed extremely high durability, with a luminous intensity retention rate of 97.4% after 1000 hours of aging, which is much better than the comparative example. In-depth analysis found that this excellent stability is due to the multiple synergistic protection system developed by the present invention. The precise ratio of the UV stabilizer forms a wide spectrum protection, and the synergistic effect of the three antioxidants establishes a multi-level protection network of "steric hindrance-free radical capture-peroxide decomposition".
[0196] Furthermore, the interface performance test revealed an important discovery: the present invention forms a unique semi-interpenetrating network structure inside the material through the introduction of glycidyl methacrylate and a special three-stage drying process. This structure not only provides excellent interface bonding strength, but also significantly improves the overall stability of the material. In particular, the interface bonding strength retention rates of Examples 2-4 are all over 94%, confirming the effectiveness of this structural design.
[0197] Finally, the most significant technical breakthrough of the present invention is the realization of the unity of "high efficiency-high uniformity-high stability". Through infrared spectroscopy and X-ray photoelectron spectroscopy analysis, it was confirmed that the chemical bonding between the ligand and the matrix was formed on the surface of the quantum dots. This strong interaction not only improves the dispersion stability of the quantum dots, but also promotes the energy transfer efficiency. Transmission electron microscopy observations show that the light diffuser forms an ordered hierarchical structure in the matrix. This structure optimizes the light propagation path at the microscopic scale and is the key to achieving high uniformity.
[0198] In summary, the present invention has achieved comprehensive breakthroughs in multiple technical indicators through precise design of material components and optimized regulation of process parameters. In particular, Example 2 exhibits the best comprehensive performance and can be used as a preferred embodiment of the present invention. These achievements provide new technical ideas for the development of high-performance quantum dot diffusion plates.
[0199] Example 3 uses the highest dosage of core-shell structure quantum dots (core layer CdSe 18 parts by weight, shell layer ZnS 9 parts by weight) and the largest particle size light diffuser combination, showing unique performance characteristics:
[0200] The dynamic light scattering test results show that the particle size distribution of quantum dots is extremely concentrated, D90 / D10=1.15, indicating excellent dispersion. Through transmission electron microscopy observation, it was found that the quantum dots formed a regular hexagonal stacking structure in the matrix. This orderly arrangement helps to improve the luminous efficiency.
[0201] [Table 3] Structural characterization and mechanical properties test results
[0202]
[0203]
[0204] [Table 4] Thermal analysis and microstructure characterization
[0205]
[0206] In-depth analysis of Example 3 revealed the following key findings:
[0207] First, through dynamic mechanical thermal analysis (DMA), it was found that Example 3 had only one tanδ peak in the range of -50°C to 150°C, and the peak temperature (68.5°C) was closest to the theoretical prediction value, indicating that the material had excellent compatibility. This good compatibility is due to the new compatibility system adopted in the present invention, which effectively regulates the interface between the quantum dots and the matrix.
[0208] Secondly, the synchrotron radiation small angle X-ray scattering (SAXS) study found that the phase separation scale of Example 3 was the smallest (15.2nm) and the distribution was the most uniform. This result confirms that the dispersion system developed by the present invention can effectively inhibit the agglomeration of quantum dots and ensure the uniformity of luminescence performance. In particular, when the phase separation scale is less than 20nm, the spatial distribution of quantum dots is more ideal, which is conducive to improving energy conversion efficiency.
[0209] Furthermore, it was observed through atomic force microscopy (AFM) phase imaging that Example 3 formed a unique "core-shell-transition layer" three-layer structure, and the thickness of the transition layer was about 2-3nm. This fine interface structure not only provides good stress buffering, but also achieves efficient energy transfer. Scanning tunneling microscopy (STM) testing further confirmed that there is a regular molecular chain orientation in the transition layer, and this ordered structure is one of the key factors in achieving high luminous efficiency.
[0210] Finally, through thermogravimetric-differential thermal analysis (TG-DTA), it was found that Example 3 showed the highest thermal stability, with a decomposition temperature of 285°C. It is particularly noteworthy that no obvious thermal effect was observed in the range of 180-220°C, indicating that the material has an excellent processing window. This good thermal stability is due to the multiple stabilizer system developed by the present invention, which significantly improves the heat resistance of the material through synergistic effects.
[0211] In terms of mechanical properties, Example 3 exhibits the best comprehensive mechanical properties, with a tensile strength of 45.6 MPa and an elongation at break of 180%. Through dynamic mechanical analysis, it was found that the ratio of storage modulus to loss modulus remained stable over the entire test temperature range, indicating that the material has excellent mechanical stability. This excellent mechanical property is derived from the new cross-linking system used in the present invention, which provides sufficient strength while maintaining appropriate toughness.
[0212] In summary, Example 3 achieves ideal results in optical properties, thermal stability, mechanical properties and other aspects through optimized formulation design and precise process control. In particular, its unique microstructure design provides new ideas for the development of high-performance quantum dot materials. These test results not only verify the feasibility of the present invention, but also reveal the inherent mechanism of material performance improvement, providing important theoretical guidance for subsequent research.
[0213] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. High uniformity quantum dot diffusion plate High uniformity quantum dot diffusion plate, characterized in that: By weight, it includes the following components: 920-940 parts by weight of acrylic copolymer matrix, 20-30 parts by weight of CdSe / ZnS core-shell structure quantum dots, 25-35 parts by weight of light diffuser system, and 12-18 parts by weight of functional additive combination; The acrylic copolymer matrix is composed of the following monomers: 455-475 parts by weight of methyl methacrylate, 270-288 parts by weight of butyl acrylate, 134-144 parts by weight of styrene, and 44-50 parts by weight of glycidyl methacrylate.
2. The quantum dot diffuser plate according to claim 1, characterized in that: The CdSe / ZnS core-shell structure quantum dots include: The core layer CdSe is 16-18 parts by weight, with a particle size of 3.3-3.7 nm; The shell layer contains 7-9 parts by weight of ZnS and has a shell layer thickness of 0.4-0.6 nm.
3. The quantum dot diffuser plate according to claim 1, characterized in that: The light diffuser system comprises: Barium sulfate 11-13 parts by weight, particle size 75-85nm; 9-11 parts by weight of silicon dioxide, with a particle size of 95-105 nm; 7-9 parts by weight of polymethyl methacrylate microspheres, with a particle size of 2.8-3.2 μm.
4. The quantum dot diffuser plate according to claim 1, characterized in that: The functional additive combination comprises: 2.5-3.5 parts by weight of UV stabilizer compound system; 3.5-4.5 parts by weight of antioxidant synergistic system; Surface conditioner 7-9 parts by weight.
5. The quantum dot diffuser plate according to claim 4, characterized in that: The UV stabilizer compounding system comprises: 1577 1.6-2.0 parts by weight; 329 0.9-1.5 parts by weight; The antioxidant synergistic system comprises: BHT 1.4-1.8 parts by weight; 168 1.2-1.6 parts by weight; PS 802 0.9-1.1 parts by weight; The surface conditioner comprises: L-7602 1.8-2.2 parts by weight; F-127 1.8-2.2 parts by weight; 4-methoxyphenol 1.8-2.2 parts by weight; 1.8-2.2 parts by weight of polymethacrylate sodium salt.
6. The method for preparing a quantum dot diffusion plate according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step (1): preparing an acrylic copolymer matrix; Step (2): preparing a quantum dot diffusion layer; Step (3): bonding the quantum dot diffusion layer to a substrate.
7. The preparation method according to claim 6, characterized in that: The step (1) comprises: (1.1) Purifying the monomers by vacuum distillation at a pressure of 90-110 mmHg, wherein the distillation temperature of methyl methacrylate is 33-37° C., the distillation temperature of butyl acrylate is 63-67° C., and the distillation temperature of styrene is 43-47° C.; (1.2) Methyl methacrylate, butyl acrylate, styrene and glycidyl methacrylate are added dropwise in order at 70-80° C. according to the formula ratio, and 2.8-3.2 parts by weight of azobisisobutyronitrile are added, and the mixture is reacted at 70-80° C. for 3.5-4.5 hours.
8. The preparation method according to claim 6, characterized in that: The step (2) comprises: (2.1) Ultrasonic dispersion of the light diffuser in toluene at a frequency of 35-45 kHz, a temperature of 23-27° C., and a time of 25-35 minutes; (2.2) adding quantum dot dispersion and functional additive combination in sequence, stirring and mixing at 130-170 rpm for 60 minutes; (2.3) Add the acrylic copolymer prepared in step (1) and stir at 30±2°C for 120 minutes.
9. The preparation method according to claim 6, characterized in that: The quantum dot diffusion layer obtained in step (2) is dried in three stages: The first stage: drying at 35-45℃ for 12-18 minutes; The second stage: drying at 55-65℃ for 18-22 minutes; The third stage: drying at 75-85℃ for 8-12 minutes.
10. The preparation method according to claim 6, characterized in that: The step (3) comprises: (3.1) Plasma cleaning of the substrate at a power of 35-45 W for 25-35 seconds; (3.2) Laminating at 83-87°C, 0.55-0.65 MPa for 2.5-3.5 minutes; (3.3) After naturally cooling to room temperature, perform aging treatment at 55-65°C for 22-26 hours.
Citation Information
Patent Citations
High-stability micro-foaming quantum dot diffusion plate and preparation method and application thereof
CN114355491A
High-water-oxygen-barrier quantum dot diffusion composite material and preparation method and application thereof
CN117382277A
High-temperature-resistant and aging-resistant quantum dot diffusion plate and preparation method thereof
CN118254441A
POK quantum dot diffusion plate and preparation method thereof
CN118271825A
Optical diffusion plate having cell structure, preparation method therefor, and application thereof
WO2023165201A1